2019
DOI: 10.1159/000496983
|View full text |Cite
|
Sign up to set email alerts
|

Cup-Shaped Tooth Wear Defects: More than Erosive Challenges?

Abstract: Background/Aim: The underlying mechanism of the development of cups and grooves on occlusal tooth surfaces is still unclear. The aim of this study was to evaluate factors contributing to in vitro cup formation, in order to elucidate the clinical process. Methods: A total of 48 extracted human molar teeth were exposed to acidic aqueous solutions at pH of 4.8 and 5.5 in constant motion, in combination with different loading conditions: no load (0N group, control), 30 N (30N group) or 50 N (50N group) (n = 8 per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
3
11
0
Order By: Relevance
“…However, it is unclear whether cupped lesions expose the dentine. Rather, in vitro studies have shown that the bottom of cupped lesions can also be located in the enamel [ 29 ]. Similar results were observed in an electron microscopic study with replicas of cupped lesions in patients [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear whether cupped lesions expose the dentine. Rather, in vitro studies have shown that the bottom of cupped lesions can also be located in the enamel [ 29 ]. Similar results were observed in an electron microscopic study with replicas of cupped lesions in patients [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, functional cusps usually occlude into a fossa, potentially allowing additional support during compared with nonfunctional cusps (Cavel, 1985). Various behavioral factors may also influence chipping and wear patterns, with many species having developed specialized ways to minimize damage (Hatt et al, 2019;Hatt et al, 2019;Schulz-Kornas et al, 2019;Nakamichi et al, 1998;Allritz et al, 2013;Ito et al, 2017;Ruben et al, 2019). The present results indicate interspecific behavioral and dietary differences do not affect the overall relationship between nonfunctional cusps and enamel chipping, to suggest a strong phylogenetic (morphological or masticatory) influence.…”
Section: Discussionmentioning
confidence: 62%
“…Second, a history of reflux esophagitis and frequent consumption of acidic foods was confirmed only by inquiry. According to an in vitro study using extracted teeth, an increase in dental attrition affecting the enamel was observed at a pH of 4.8, but not at pH 5.5 [40]. Tooth wear of the enamel may be greatly influenced by bruxism under low pH conditions, and further investigation is needed.…”
Section: Discussionmentioning
confidence: 99%